Critical Success Factors for Startups : A Study on Mumbai-Pune Region, Maharashtra, India - Palkar, Apoorva; Hari, K. S. (AMC Indian Journal of Entrepreneurship, 2021)
India featuring in the top five largest economies in the world relies heavily on the success of startup business enterprises for continuous economic growth and employment generation. Government of India through Startup India Initiative since 2015 has increased its focus on creating an inclusive environment for the growth and success of Startup Business Enterprises. This has shown positive outcome in terms of number of new startups and the amount of investment flown to this crucial sector of the economy. The present study was an attempt to understand the key success factors for startup in India through a study on selected startups in Mumbai-Pune region of western India, the traditional manufacturing and financial capital of India. Our analysis using the various ranking methods and Analytical Hierarchy Process helped us to identify entrepreneurship as the major success factor for new startups in India. This has larger policy implication for the promotion of entrepreneurship in this crucial sector.